Development Trends and Practical Approaches for Personalized Learning in the Era of Digital Transformation in Education - Xie, Yanping (Journal of Educational Research and Policies, 2025)
Digital transformation represents an inevitable trend in social and historical development, presenting both new opportunities and challenges for educational innovation. As digital technology integrates with education, personalized learning—a new “human-centered” learning model—has increasingly highlighted its essence, characteristics, and value. Under digital transformation, personalized learning evolves from “individual experience” to “collective intelligence collaboration”; from “content-centric” to “ecological synergy”; from “fixed learning” to “dynamic generation”; and from “focusing on teaching outcomes” to “pursuing the educational process.” Within this developmental framework, the following practical approaches for personalized learning are proposed: returning to the essence of education to advance individual development; addressing student differences to foster learning intelligence; synergizing humans and machines to achieve human-machine symbiosis; and improving operational mechanisms to ensure resource quality.